CLEM with Commercially Available Reagents to Facilitate Immunolocalization. (July 2020) - Cummins, Leslie; Tu, Vincent; Mayoral, Joshua; Weiss, Louis M.; Macaluso, Frank P.; DesMarais, Vera
Abstract: Abstract : There is often a need to locate the same cellular structure of interest in light and electron microscopy, which can be a difficult task. Here we present a method that uses only commercially available reagents and standard epi-fluorescence and transmission electron microscopy (TEM) technology to make correlative light and electron microscopy (CLEM) available to a large group of researchers without specialized CLEM hardware. This was achieved by seeding cells on photo-etched gridded cover slips and staining the protein to be localized with a secondary antibody coupled to both a fluorophore and 10 nm gold. The presence of the grid allowed for the alignment of light microscopy images with TEM images and the double-labeled antibody revealed co-localization of the fluorophore with gold particles.